Eksistensi mahasiswa dalam menggunakan aplikasi tiktok (studi kasus pada mahasiwa semester V ilmu komunikasi Universitas Veteran Bangun Nusantara Sukoharjo) - Dolarosa, Fernanda Ilsavia; Suryo, Herning; Riyanto, Buddy (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2023)
Seeing the use of TikTok, which is widely used by millions of people, students of theBangun Nusantara Sukoharjo University (Univet) are interested in downloading theTikTok application, because the Tik Tok application is believed to be a means ofcommunication as well. In the TikTok application there are lots of interesting featuressuch as funny face effects, songs of various genres, and of course in Tik Tok there arefeatures like, comment, direct message. This research is a descriptive qualitativemethod. This study describes the existence of students in the fifth semester of Science.Univet Sukoharjo communication in using the TikTok application. Theory According toAgus Elly Ermayani's theory, (2004: 63), the presence of social media seemsinseparable from the lives of teenagers, because at this time almost every day hoursminutes and even seconds do not stop for status updates. Social networks are usuallyused by teenagers to talk about life. they even show their existence everyday by showingwhere they go or the places they like and posting photos. Things like this are very clearto see the role of social media in the search for existence for adolescents. Tik Tok, as anapplication for sharing short and unique videos, has become one of the most popularapplications. The results of this study are that fifth semester students of Univetcommunication science use the Tik Tok application as a means of self-existence,because Tik Tok is considered capable of being a distributor of information and achannel of its existence compared to other applications/social media. By takingadvantage of creating content in the Tik Tok application, V semester students in Univetcommunication science are able to get a lot of followers so that they can easily conveyinformation and easily communicate with the general public, and also easily makethemselves more useful to many people because of quality content .Keywords: Existence, use, students, TikTok application